Interfacial characteristics of Cu–Fe laminate fabricated by solid state welding. (April 2014) - Yang, Y. H.; Lin, G. Y.; Chen, D. D.; Wang, X. Y.; Wang, D. Z.; Yu, H. C.
<x content-type="archive" xml:space="preserve">Abstract</x> Solid state welding was employed to join low intersolubility metal couple Cu–Fe, and the microstructure and mechanical properties of the joints were investigated. The interface was free of defects. Scanning electron microscopy, energy dispersive spectrometry, atomic force microscopy and nanoindentation results revealed that a potential area of pseudo-binary alloy was present at the faying surface, where nanoscale particles were moved to the opposite side by facilitated diffusion. Owing to the mechanism of microcontact and facilitated diffusion, the interfacial strength was improved.